2014
DOI: 10.1002/ijc.28656
|View full text |Cite
|
Sign up to set email alerts
|

TLR4/PKC‐mediated tight junction modulation: A clinical marker of chemotherapy‐induced gut toxicity?

Abstract: Chemotherapy‐induced gut toxicity is a major clinical and economic burden to oncology practice. The mechanisms responsible for its development are ill defined, hampering the development of therapeutic interventions. In light of newly published research foci and clinical practice guidelines in supportive care in cancer, there has been renewed interest in the role tight junctions play in the pathobiology of chemotherapy‐induced gut toxicity. Several preclinical studies have identified molecular defects in intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 120 publications
2
26
0
Order By: Relevance
“…Several claudin genes were significantly affected and DOX-treated piglets showed enhancement of GO cellular component tight-junction gene set expressions, with claudin 3, 6, 11, 14, and 16 in the leading edge subset (nominal p value 0.011). These findings are supported by previous reports documenting changes in tight-junction protein composition, expression, and function following chemotherapy (table 1) [13,14,47]. The exact role of tight-junction proteins in mucositis, as well as their interaction with other mediators such as MMP and proinflammatory cytokines, is an area of intense investigation [47,48].…”
Section: Discussionsupporting
confidence: 75%
“…Several claudin genes were significantly affected and DOX-treated piglets showed enhancement of GO cellular component tight-junction gene set expressions, with claudin 3, 6, 11, 14, and 16 in the leading edge subset (nominal p value 0.011). These findings are supported by previous reports documenting changes in tight-junction protein composition, expression, and function following chemotherapy (table 1) [13,14,47]. The exact role of tight-junction proteins in mucositis, as well as their interaction with other mediators such as MMP and proinflammatory cytokines, is an area of intense investigation [47,48].…”
Section: Discussionsupporting
confidence: 75%
“…When mucosal homeostasis is disrupted, PKC signalling participates in TLR-induced downstream events [20, 35, 36]. Cario et al suggested that TLR2 activation enhances ZO-1 via PKC, and Gibson et al reported that TLR2 plays a critical role in maintaining intestinal mucosal integrity during infections by bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these findings, the interaction between the gut microbiome and innate mucosal immune system has also gained interest, with particular emphasis on the impact of toll-like receptor (TLR) signaling (8)(9)(10). TLRs are a family of transmembrane protein receptors recognising a diverse range of signals on exogenous and endogenous substances considered to be 'dangerous', and hence warranting activation of the innate immune system for host survival (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%